Using English medium instruction to teach a general course in a College of Business and Management - Oraif, Iman; Alrashed, Mohammed (Frontiers in Psychology, 2022)
Even though learning can be complex when using a language other than one’s mother tongue, the English-medium communicative approach has been widely adopted in Saudi universities over recent years. Many university majors in Saudi Arabia are now taught through the medium of English rather than Arabic, as was previously the case. This also applies to the social and natural sciences. Moreover, instructors are trying to avoid using any Arabic in class, given that English has become the lingua franca in many domains. Thus, the current study seeks to understand how students in the College of Business and Management at Al-Imam University, Riyadh, Saudi Arabia feel about English being used as the medium of instruction (EMI) as they study English for specific purposes (ESP). Also examined is the relationship between their previous language test scores and current reflections. Twenty-four female students participated in a survey adapted from Wong (2010), generating results to reveal a positive attitude to using EMI on an ESP course. However, no relationship was found between the participants’ language assessment test scores and current feelings.